The Effect of Problem Possing Assisted Mind Mapping on Problem Solving and Reasoning Skill in Terms of Cognitive Style - Fitriana Eka Chandra (Universitas Islam Jember, 2020)
The purpose of this research was to investigate the effects of Problem Posing learning facilitated by Mind Mapping toward problem solving and reasoning abillity based on students’ cognitive style. Totally, there were 106 students involved in the study which comprised of 42 students from VIIE class of SMPN 7 Jember as experimental group (PPMM class), 42 students from VIIF class of SMPN 7 Jember as the first control group (PP1 class) and 32 students from VIID class of SMPN 1 Arjasa as the second control group (PP2 class). Before giving the treatment, students was given GEFT test to know the kind of cognitive style that they have. There are two kind of student’s cognitive style in this paper i.e. field-dependent and field-independent cognitive style. The study found that student’s problem solving and reasoning abillity of PPMM class are better than PP class. Moreover, problem solving and reasoning abillity of field independent students is better than field dependent students. Keywords: problem possing, mind mapping, problem solving, reasoning, and cognitive style